RHABDOMYOMA OF THE NASOPHARYNX (CLINICAL OBSERVATION) - D. M. Mustafaev (Опухоли головы и шеи)
Rhabdomyoma of the nasopharynx is an extremely rare disease. Currently, there are only isolated cases of rhabdomyoma of the nasopharynx described in literature. Information on the clinical picture and course of the disease is very poor. The author presents his own clinical observation of a rare localization of rhabdomyoma in the nasopharynx. Analysis of literature data and clinical observation allowed the author to conclude that rhabdomyoma of the nasopharynx has a relatively favorable prognosis given early detection, benign quality of the disease, and availability of radical surgery.